2017
DOI: 10.1111/inr.12369
|View full text |Cite
|
Sign up to set email alerts
|

Disaster preparedness among nurses: a systematic review of literature

Abstract: The findings from this review place an emphasis on hospitals to implement policies to address lack of preparedness among their employees. Furthermore, this review highlights the benefit of further research and provision of well-grounded disaster exercises that mimic actual events to enhance the preparedness of the nursing workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
264
2
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(296 citation statements)
references
References 33 publications
(217 reference statements)
20
264
2
10
Order By: Relevance
“…So, these study results concerning the nurses’ perceptions of disaster core competencies are compatible with the results of other studies (Labrague et al. , ). Similarly, Labrague et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So, these study results concerning the nurses’ perceptions of disaster core competencies are compatible with the results of other studies (Labrague et al. , ). Similarly, Labrague et al.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Labrague et al. () investigated 17 publications that measure ‘nurses’ preparedness for disaster response’ in a systematic review and a common result of all studies is reported that ‘nurses are inadequately prepared for disaster response’.…”
Section: Discussionmentioning
confidence: 99%
“…September is National Preparedness Month, which provides a time each year to focus on being prepared for disasters, including weather‐related events, terrorist attacks, and disease outbreaks, among others. Although nurses are critically important to disaster response, evidence has indicated that they are not adequately prepared for these events . As part of disaster preparedness, it is imperative that health care leaders provide training to nurses and other health care personnel on emergency policies and procedures and treating disaster survivors.…”
mentioning
confidence: 99%
“…Preparedness exercises are a key component of training that contribute to team building and teamwork. Exercises have been shown to improve personnel's knowledge of emergency events, policies, and procedures; perception of disaster skills; understanding of roles; and overall competence and confidence . In addition, exercises can help health care leaders test their emergency plans, protocols, and procedures; identify problem areas; and make improvements .…”
mentioning
confidence: 99%
See 1 more Smart Citation